Efek Perlakuan Cold Plasma terhadap Umur Simpan Cabai Rawit (Capsicum frutescens L.) - Yohanes Aris Purwanto; Nurul Hanifah; Anto Tri Sugiarto (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Cayenne pepper is a perishable product. One of the damages that can cause spoilage in cayenne pepper is microorganisms. This study examines the quality change of cayenne pepper during storage. The research design employed in this study was a complete factorial randomized design with two factors: voltage levels, comprising 8,00, 9,20, and 10,40 kV, and treatment times of 20, 40, and 60 seconds. Cold plasma effectively reduced microorganisms and did not significantly affect weight loss and color value during storage. Plasma voltage levels significantly influenced hardness, total dissolved solids, and vitamin C content. The treatment with cold plasma at 9,20 kV for 40 seconds was considered the most effective in preserving chili quality. Cold plasma reduced weight loss and maintained chili color, hardness, total dissolved solids, and vitamin C content. The total plate count of cayenne pepper with cold plasma at 9,20 kV for 40 seconds is 6,55 x 105 colony/g. Cold plasma extended the shelf life of cayenne pepper for up to 12 days.